A multi-physics reduced order model for the analysis of Lead Fast Reactor single channel. (January 2016) - Sartori, Alberto; Cammi, Antonio; Luzzi, Lelio; Rozza, Gianluigi
Highlights: Multi-physics reduced order modelling for the single-channel analysis of Lead Fast Reactor. Reduced Basis method, with basis functions computed by Proper Orthogonal Decomposition. Physical and geometrical parametrization. Non-linear coupling between neutronics and heat transfer phenomena. Abstract: In this work, a Reduced Basis method, with basis functions sampled by a Proper Orthogonal Decomposition technique, has been employed to develop a reduced order model of a multi-physics parametrized Lead-cooled Fast Reactor single-channel. Being the first time that a reduced order model is developed in this context, the work focused on a methodological approach and the coupling between the neutronics and the heat transfer, where the thermal feedbacks on neutronics are explicitly taken into account, in time-invariant settings. In order to address the potential of such approach, two different kinds of varying parameters have been considered, namely one related to a geometric quantity (i.e., the inner radius of the fuel pellet) and one related to a physical quantity (i.e., the inlet lead velocity). The capabilities of the presented reduced order model (ROM) have been tested and compared with a high-fidelity finite element model (upon which the ROM has been constructed) on different aspects. In particular, the comparison focused on the system reactivity prediction (with and without thermal feedbacks on neutronics), the neutron flux and temperature field reconstruction, and on the computational time. The outcomes provided by the reduced order model are in good agreement with the high-fidelity finite element ones, and a computational speed-up of at least three orders of magnitude is achieved as well.